2016
DOI: 10.1016/j.micres.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphate solubilizing Burkholderia spp. for successful colonization and growth promotion of Lycopodium cernuum L. (Lycopodiaceae) in lateritic belt of Birbhum district of West Bengal, India

Abstract: Profuse growth of Lycpodium cernuum L. was found in phosphate deficient red lateritic soil of West Bengal, India. Interaction of vesicular-arbuscular mycorrhiza (VAM) with Lycopodium rhizoids were described earlier but association of PGPR with their rhizoids were not studied. Three potent phosphate solubilizing bacterial strains (P4, P9 and P10) associated with L. cernuum rhizoids were isolated and identified by 16S rDNA homologies on Ez-Taxon database as Burkholderia tropica, Burkholderia unamae and Burkholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 25 publications
4
48
1
2
Order By: Relevance
“…A large number of studies have shown that application of PGPR enhances the tolerance of plants to multiple abiotic stresses such as nutrient deficiency, water deprivation and soil alkalization (Dey et al 2004;Sherameti et al 2008;Zhou et al 2016), indicating that beneficial soil bacteria can be employed to increase plant's absorption of nutrient elements. B. cepacia is one of the more important PGPR that have been widely used to improve plant growth, stress adaption and pathogen invasion (Singh et al 2013;Zhao et al 2014;Ghosh et al 2016). In this study, a novel role of B. cepacia JFW16 in regulating plant uptake of Fe was observed, which was positively associated with the activated plant's Fe acquisition systems.…”
Section: Accumulated In Rootsmentioning
confidence: 70%
See 1 more Smart Citation
“…A large number of studies have shown that application of PGPR enhances the tolerance of plants to multiple abiotic stresses such as nutrient deficiency, water deprivation and soil alkalization (Dey et al 2004;Sherameti et al 2008;Zhou et al 2016), indicating that beneficial soil bacteria can be employed to increase plant's absorption of nutrient elements. B. cepacia is one of the more important PGPR that have been widely used to improve plant growth, stress adaption and pathogen invasion (Singh et al 2013;Zhao et al 2014;Ghosh et al 2016). In this study, a novel role of B. cepacia JFW16 in regulating plant uptake of Fe was observed, which was positively associated with the activated plant's Fe acquisition systems.…”
Section: Accumulated In Rootsmentioning
confidence: 70%
“…However, alkaline soils become the major constraints to the distribution and biomass of crop in agriculture Jia et al 2015). Recently, soilborne bacteria Burkholderia cepacia has been attracted considerable attentions due to its diverse roles such as enhancement of nutrient use efficiency and control of fungal infection in host plants (Singh et al 2013;Zhao et al 2014;Ghosh et al 2016). Here, we examined the activity of B. cepacia (strain JFW16) in plant Fe assimilation.…”
Section: Research Articlementioning
confidence: 99%
“…The results are in agreement with previous study reporting ACC deaminase activity of endophytic bacteria in Phytolacca Americana (Zhang et al 2015). Phosphate solubilization potential is very common among endophytic bacteria (Ghosh et al 2016). In this study, a clear zone around the isolates RM2, RM3, and RM colonies in Pikovskaya medium indicated the phosphate solubilization potential of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…(Burkholderiaceae) and Bacillus sp. (Bacillaceae) are also reported to be effective RP solubilizers, both in vitro assays (Gomes et al, 2014; Ghosh et al, 2016) or inoculated in plants (Baig et al, 2014; Stephen et al, 2015; Wahid et al, 2016). Furthermore, Burkholderia and Herbaspirillum are both diazotrophs.…”
Section: Discussionmentioning
confidence: 99%